Pelatihan Pengenalan Cara Kerja Search Engine Marketing untuk Platfom Digital Marketing kepada siswa SMAN 16 Bandung - Akbar, Imannudin; Nursyanti, Reni; Ramadhani, Muhammad Wahyu; Setiawan, Dani (Jurnal Pengabdian Masyarakat Tapis Berseri (JPMTB), 2025)
Over time, companies have begun transitioning their marketing systems from conventional methods to modern approaches by leveraging the internet. This shift is further supported by the ease of accessing social media, conducting transactions, and communicating online, all of which make internet-based marketing increasingly advantageous. The massive number of internet users and the high engagement with digital media have given rise to new business potentials and opportunities, widely known as digital marketing.Digital marketing strategies are estimated to influence up to 78% of a business unit’s competitive advantage in promoting its products. It enables adaptive digital relevance across a series of marketing activities, institutions, processes, and customers. This, in turn, drives a 20% annual growth in customers transitioning to digital platforms, with younger users becoming a dominant group of consumers.Search Engine Marketing (SEM) is an online marketing strategy designed to increase website visibility on search engine results pages. SEM serves as an effective promotional tool and is one of the fastest ways to direct potential consumers to a website, as effective SEM can position a site on the first page of search engine results.